Green Synthesis and Anti-microbial Activities of Some Thiazole-imino Derivatives - Singh, Satbir; Raj, Seema; Sharma, Sunil; Sucheta; Yadav, Vijay (Orbital: The Electronic Journal of Chemistry, 2023)
The ring forming reaction of furfural imine (A) and substituted acetophenone (B) via a greener approach resulted in the synthesis of thiazole-imino derivatives (C1 – C5). The compound A was synthesized by green method using acetic acid in aqueous media where conc. Sulfuric acid was avoided. The final compounds (C1-C5) were again synthesized in aqueous media avoiding use of organic solvents. The resultant compounds were characterized and distinguished from their precursors by elemental analysis, 1H-NMR, 13C-NMR and IR spectral studies. The in-vitro activities of the final compounds (C1-C5) depicted that they are all appreciably active against bacterial strains S. aureus, B. subtilis and fungal strains C. albicans, C. glabrata. Ciprofloxacin and Itraconazole were used as the control drugs for anti-bacterial and for anti-fungal activities; respectively. As compared to the other analogues, compound C2 (R = NO2) and C4 (R = Cl) showed best activities against the bacterial and fungal strains; respectively.